Perbandingan Antara Arsitektur Perangkat Lunak Microservices dan Monolith (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
A comparative analysis is the process of comparing items to one another and distinguishing their similarities and differences. Big Data is a set of massive data that has 3 characteristics in general. The characteristic is volume, variety, and velocity. In order to process such a big amount of data, we need some kind of software that can efficiently process the data with an available resource. Two of much architectural style on software development known are microservices and monolithic architecture. There are many differences between microservices and monolithic architecture that need to be considered when choosing the right architecture to use. The study will compare between microservices and monolithic architecture to decide which architecture would be preferred to handle and process many data such as big data. The result showed that microservices has less and distributed resource usage compared with monolithic architecture.